Pengaruh Massage Effleurage Dan Relaksasi Nafas Dalam Terhadap Nyeri Punggung Ibu Hamil Trimester III - Fitriana, Lala Budi; Vidayanti, Venny (Bunda Edu-Midwifery Journal (BEMJ), 2019)
Low Back pain experienced by pregnant women results in limited mobility, which hinders the activity of pregnant women such as caring for children, influencing maternal work and insomnia. Low back pain also causes fatigue and irritability. Massage effleurage and deep breath relaxation are alternative Therapies to reduce low back pain in third trimester pregnant women. This study aimed to determine the effect of massage effleurage and deep breathing relaxation on low back pain in third trimester pregnant women. This study was a quasi-experimental design with pre-test and post-test nonequivalent control group. This study involved by 32 respondents who were divided into 2 groups and 16 respondents for each group. This study conducted at Puskesmas Jetis Yogyakarta. The sampling technique was consecutive sampling. The instrument to measured low back pain was Numerical Rating Scale. The Study analysis used paired t-test. The results of the study were the mean pre and post back pain scale in the group given massage effleurage was 4.81 and 2.06. The average pre and post back pain scale in the group given deep breath relaxation was 4.05 and 3.06. The p-value in the massage effleurage group was 0,000. The p-value in the deep breathing relaxation was 0,000. The conclusion of the study was Massage effleurage and deep breathing relaxation were effective intervention to reduce low back pain of pregnant women in the third trimester.